Metabolic correction of dyslipidemia in patients with nonalcoholic fatty liver disease as a new therapy policy - Stel'makh, V V; Kozlov, V K (Terapevtic̆eskii arhiv, 2013)
To study the impact of infusion therapy with the metabolic modulator remaxol on lipid metabolic parameters and target organ (liver, kidney) function in metabolic syndrome (MS). The investigation enrolled 90 patients (54 men and 36 women) with primary nonalcoholic steatohepatitis that was associated with insulin-resistance and MS; their age was 21 to 77 years. Every day the study group patients (n = 50) took as a component of combination therapy the metabolic hepatoprotective modulator remaxol intravenously in a dropwise manner in a dose of 400 ml once daily; the comparison group patients (n = 40) received ademetionine 400 mg diluted in 400 ml of isotonic sodium chloride. The duration of infusion therapy was 11 days. Infusion therapy with remaxol caused a pronounced blood lipid composition-regulating effect, by reducing the level of major atherogenic lipids (total cholesterol, triglycerides) and improving liver function and renal nitrogen-excreting and filtration function in patients with Stage IV diabetic nephropathy in the presence of MS. Therapy with the metabolic hepatoprotective modulator remaxol ensures reliable metabolic control and multifactorial correction of risk factors of organ lesions in MS: cardio-, hepato-, and nephroprotection.